2013
DOI: 10.1039/c3cy00062a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic water oxidation on ZnO photoanodes in a borate buffer electrolyte

Abstract: Solar fuels can be produced from photocatalytic, photoelectrochemical or photovoltaic-electrochemical splitting of H 2 O and conversion of CO 2 . In these processes, the water oxidation reaction is involved. The water oxidation reaction is complicated with transfer of 4 electrons and 4 protons. Calculation results showed that the free energy change of the rate-controlling step of water oxidation is as high as B0.6 eV at the overpotential of 0.7 V on the TiO 2 surface, 1 and transient absorption spectroscopy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[16] A recent study also showed that the activity of photoanodes in ab uffered phosphate electrolyte, as ap roton-accepting electrolyte (PAE), was higher than that in an unbuffered sulfate electrolyte. [18] These results highlight the important role of the PAE during PEC water oxidation. [18] These results highlight the important role of the PAE during PEC water oxidation.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…[16] A recent study also showed that the activity of photoanodes in ab uffered phosphate electrolyte, as ap roton-accepting electrolyte (PAE), was higher than that in an unbuffered sulfate electrolyte. [18] These results highlight the important role of the PAE during PEC water oxidation. [18] These results highlight the important role of the PAE during PEC water oxidation.…”
Section: Introductionmentioning
confidence: 78%
“…[17] Another study reported that the water oxidation onset potentialh ad an egative shift of about 0.2 Vb yi nsitu treatment or immersion of ZnO photoanode in borate buffer. [18] These results highlight the important role of the PAE during PEC water oxidation.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Among the many inorganic photocatalysts applied for water splitting (TiO 2 , WO 3 , ZnO, α ‐Fe 2 O 3, BiVO 4 , etc. ), tantalum‐based oxynitrides among the few n ‐type semiconductors with close to an ideal electronic configuration, as illustrated in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 ZnO is well known to have energy-band structure and physical properties similar to TiO 2 . [9][10][11] In addition, ZnO has the advantages of low-temperature preparation, controllable structural design, and high carrier transport, especially its good electron mobility (for ZnO, it is 115-155 cm 2 V −1 s −1 ; for TiO 2 , it is 10 −5 cm 2 V −1 s −1 ). [12][13][14][15][16][17][18] ZnO has the capability of growing with many different types of morphologies including wires, rods, tubes, particles and power shapes at the nanoscale, [14][15][16][17][18][19] which can be prepared through different approaches, for example, chemical vapor deposition, 20 sputtering, 21 thermal spraying, 22 and the commonly used wet-chemical routes, 23 while the preparation of porous ZnO nanoparticles by a chemical template-free method has been scarcely reported.…”
mentioning
confidence: 99%